2014
DOI: 10.1002/we.1796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea surface temperature accuracy on offshore wind resource assessment using a mesoscale model

Abstract: Offshore wind simulations were performed with the Weather Research and Forecasting (WRF) model driven by three different sea surface temperature (SST) datasets for Japanese coastal waters to investigate the effect of the SST accuracies on offshore wind simulations. First, the National Centers for Environmental Prediction Final analysis (FNL) (1°× 1°grid resolution) and the Operational Sea Surface Temperature and Sea Ice Analysis (OSTIA) (0.05°× 0.05°grid resolution) datasets were compared with in situ measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…In addition, wind speeds tend to be higher during the day than at night due to temperature gradients and this effect is intensified in summer. Current wind resources and capacity factors in Japan have also been estimated using meteorological models [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, wind speeds tend to be higher during the day than at night due to temperature gradients and this effect is intensified in summer. Current wind resources and capacity factors in Japan have also been estimated using meteorological models [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Hiroyuki et al () run the RAMS model through 8 and 2 km resolution simulations to investigate wind energy potential over the area of Tokyo (Japan), and found good agreement with observations, with a 4.8% prediction error on annual mean wind speed. Rather good scores were also obtained by Shimada et al () in reproducing wind data for offshore wind resource assessment over Japan after applying MM5 and WRF models with 4.5 and 1.5 km resolutions. Guilherme et al () ran the WRF model to derive wind data for Portugal using 6 and 3 km resolution, obtaining model simulation winds slightly weaker (about 5%) than the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…This study used satellite-observed sea surface temperature for estimating changes in wind speed because temperature is one of the principal climate factors and satellite-observed sea surface temperature is able to estimate variations in winds, swells, and waves [23,24]. The sea surface temperatures are the optimum interpolation sea surface temperatures (OISST), as re-analysis data based on ships, buoys, and advanced, very high-resolution radiometer in satellites [25].…”
Section: Sea Surface Temperature Datamentioning
confidence: 99%